Contributions of Screen Use on Early Language and Development Milestones in Argentinean Toddlers from Different Socioeconomic Contexts - Gago Galvagno, Lucas Gustavo (2023)
The objective of the following research was to describe the use of digital media (i.e., TV, background TV, cell phone, PC, and Tablet), presence of the adults during this activity, and its association with language, motor, and language developmental milestones and SES in the first years of life. Participants were 114 primary caregivers of toddlers between 12 and 36 months (M = 27.48 months, SD = 7.31, female = 58, low SES = 56). Parental reports of infant media use, motor and language development milestones, the Inventory of Skills Development (CDI), and the INDEC Scale (for SES) were used. The results showed that, on average, toddlers engaged for 1 h per day with TV and were passive recipients of background TV for 2 h a day, which was the most used screen. In addition, parents tend to share TV with toddlers. Language positively related with child Tablet use, book use, and TV shared with an adult, and there were negative associations with children’s cell phone and PC use alone and with an adult. For SES, having at least one basic need unsatisfied or less parental educational and occupancy was related with more background TV and use, less time sharing this type of media with toddlers, and less use and quantity of books at home. In general, there were no relations between digital media use and developmental milestones. This indicates that the excessive use of screens could relate to some early language skills, although it is necessary to investigate the context in which they are used.